Clinical chemistry principles, techniques, and correlations - Bishop, Michael L.; Fody, Edward P.; Schoeff, Larry E. (Wolters Kluwer, 2018)
This book demonstrates the how of clinical testing, and also the what, why, and when of testing correlations to help students develop the knowledge and interpretive and analytic skills they'll need in their future careers